"Liberty of Conscience" and the Jews in the Dutch Republic - Bodian, Miriam (Studies in Christian-Jewish relations, 2011)
In the popular imagination, seventeenth-century Amsterdam was an oasis of religious toleration in a conflict-ridden Europe and a city that welcomed Jews with open arms. This image is exaggerated and misleading, as scholars have long since shown. In this essay, I will examine how the interests of the Dutch ruling class, the regents, dovetailed with the interests of the governing elite of the Portuguese-Jewish community of Amsterdam to create structures of Jewish governance that were agreeable to both governing parties. While maintaining peace was one of the common interests between them, so was maintaining discipline. Neither the Dutch nor the Jewish authorities sought "liberty of conscience" in the modern sense of the term, that is, individual religious and philosophical freedom. For most, though not all, members of the Portuguese-Jewish community, this arrangement was natural and fully acceptable.